Egg Introduction During Infancy Is Associated with Lower Fat Mass Index in Early Adolescent Females. (14th June 2022) - Choudhary, Divya; Rideout, Todd; Cameron, Claire; Lehman, Heather; Oken, Emily; Rifas-Shiman, Sheryl; Wen, Xiaozhong
Abstract: Objectives: Egg consumption may play an important role in early-life growth given their high-quality protein, essential fatty acids, and micronutrients. The objective of this study was to examine the longitudinal associations of infant age at egg introduction with obesity outcomes in early childhood, middle childhood, and early adolescence. Methods: We used existing data from 1, 089 mother-child dyads from Project Viva to estimate age at egg introduction through a questionnaire completed by mothers at about 1 year postpartum (mean ± SD, 13.3 ± 1.2 months). Outcome measures included height and weight, body composition including total fat mass, trunk fat mass, and lean mass, as well as plasma adiponectin and leptin in early childhood, mid-childhood, and early adolescence. We defined childhood obesity as sex- and age-specific body mass index (BMI) ≥95 th percentile. We estimated the associations of infant age at egg introduction with risk of obesity using multivariable logistic regression and multivariable linear regression models were used for BMI z-score, body composition measures, and adiposity hormones, adjusting for maternal pre-pregnancy BMI and socio-demographics. Results: Among females only, those introduced to eggs by the 1-year survey had a lower total fat mass index (confounder-adjusted mean difference, −1.23 kg/m 2 [95% confidence interval, −2.14, −0.31]) and trunk fat mass index (−0.57 kg/m 2 [−1.01, −0.12]) in early adolescence compared with those not introduced. Similarly, among females, egg introduction in infancy was associated with lower plasma adiponectin (confounder-adjusted mean difference, −1.93 μg/mL [−3.70, −0.16]) in early childhood. However, no associations between infant age at egg introduction and risk of obesity were observed among males (confounder-adjusted odd ratio, 1.97 [95% confidence interval, 0.90, 4.30]) or females (0.68 [0.38, 1.24]) across all ages. Conclusions: Egg introduction during infancy among females was associated with lower total fat mass index in early adolescence and adiponectin in early childhood. Funding Sources: Egg Nutrition Center/American Egg Board.